PENYUSUNAN SIMTRABA (SISTEM INFORMASI MANAJEMEN TATA RUANG DAN TATA BANGUNAN) DPUPR KABUPATEN BENGKULU TENGAH - Endri Agustomi; Dedy Agung Prabowo; Eki Agustiawan (Jurnal Informatika Upgris, 2020)
Giving citizens access to information from government and non-government institutions is one form of public information disclosure. Openness of public information that has been considered difficult to reach by the public is expected to help build openness between the community and government and non-government institutions in the future. In practice, obtaining the latest, accurate and complete data requires public information disclosure. In planning and development, up-to-date data is needed, especially building and land data that can support its implementation. Therefore the Dinas Pekerjaan Umum dan Penataan Ruang (DPUPR) Bengkulu Tengah Regency responsible for building management needs to conduct building data collection activities so that the availability of information regarding building data can be met. So in terms of spatial planning and building layout so that it is faster and more effective in identifying specific problems concerning the relationship of data between one and the other that are built connected by describing the characteristics of spatial planning openly, it requires an application of Spatial Management and Building Management Information Systems or abbreviated as SIMTRABA